Thermal characteristics of louvered fins with a low-reynolds number flow - Nat Vorayos (2018)
A heat recovery system is crucial for the effective use of energy where heat rejection from production processes is unavoidable and must be reused. The response of the louvered fins to the low-Reynolds number hot gas is yet to be reported in the literature for the application of a heat exchanger on low-speed hot plume arising from heat sources in production processes. This study focuses on the effects of the louvered fin heat exchanger's design parameters, which include the louver pitch and louver angle, on the convective heat transfer, which defines the thermal interaction between the hot, buoyant, naturally-induced air and the louvered fins. The resulting Colburn factors (j) are compared with those derived under forced convection with a similar range of low Reynolds number (233 to 1024). All experiments are done on a 15:1 scaled-up model. The fin aspect ratios between the fin spacing and louver pitch are set at 0.75, 1, and 1.5, while the louver angles are set at 18°, 23°, 30°, 35°, and 40°. The Colburn factor strongly depends on the louver angle, especially at the lower range of the Reynolds number. The decreasing aspect ratio induces more hot buoyant air into the louver-formed channels, increasing the heat transfer rate. When the fin angle increases towards 30°, a larger Colburn factor is produced. However, the heat transfer characteristic drops as the angle goes beyond 30°. The highest j for the low speed flow is attained when the louver angle is 30° and the fin aspect ratio is 1. © 2010 The Korean Society of Mechanical Engineers and Springer-Verlag Berlin Heidelberg.